2020
DOI: 10.1177/2321022220918684
|View full text |Cite
|
Sign up to set email alerts
|

FDI and Economic Performance of Firms in India

Abstract: FDI contributed positively to sales, profit, employment and wages of firms in India from 2004 to 2018. Foreign capital is complementing domestic capital well embodying technology and innovations required for expansion of domestic firms in it. Foreign promoters have played quite significant economic roles among firms across production sectors in manufacturing industry in India. Besides sales, total expenses, managerial remunerations and corporation taxes, involvement of foreign promoters are statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Accordingly, H4 is accepted, indicating that BICH moderates the relationship between board remuneration and banks’ performance. Bhattarai and Negi [ 110 ], Kang and Nanda [ 111 ], Das and Mohanty [ 112 ], and Lee and Isa [ 59 ] also indicate similar findings. Finally, the results show that the moderating effect of BICH does not significantly moderate the relationship between bank specifics and FP across all models.…”
Section: Analysis and Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Accordingly, H4 is accepted, indicating that BICH moderates the relationship between board remuneration and banks’ performance. Bhattarai and Negi [ 110 ], Kang and Nanda [ 111 ], Das and Mohanty [ 112 ], and Lee and Isa [ 59 ] also indicate similar findings. Finally, the results show that the moderating effect of BICH does not significantly moderate the relationship between bank specifics and FP across all models.…”
Section: Analysis and Discussionmentioning
confidence: 63%
“…However, from the accounting viewpoint, the results report a positive link between the two, indicating that directors’ remuneration contributes to firms’ intrinsic value but does not add significantly to firms’ extrinsic value. Similarly, Bhattarai and Negi [ 110 ] indicated that managerial remunerations, among several other variables, are statistically significant factors in firms’ profitability. Das and Mohanty [ 112 ] show that the average managerial remuneration has a significant impact on regular dividend-paying behavior of Indian firms.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we measure foreign direct investment as a ratio of foreign direct investment to the gross domestic product. We hypothesize a positive effect of foreign direct investment on the financial performance of firms [83].…”
Section: Other Explanatory Variablesmentioning
confidence: 96%
“…The traditional theories of economic growth like the Solow Model did not consider FDI as a determinant of economic growth, but new growth theories have shown FDI as having both level effect and rate effect on output. FDI has also been shown to have indirect effects on economic growth through various channels such as sales, profit, employment and wages (Bhattarai & Negi, 2020).…”
Section: Introductionmentioning
confidence: 99%